Pregnancy Rate after Tubal Reanastomosis: A Case Presentation and Systematic Review - Zucha, Muhammad A.; Lutfi, Muhammad; Silawani, Supak; Feliciana, Anastasia; Astari, Pritania (IOS Press, 2022)
Sterilization is one of the preferred contraceptive techniques for couples who do not want more children. In addition, female sterilization is often indicated for women when pregnancy is contraindicated, for example, those who have Class Risk IV of a major cardiac event. Female sterilization is preferred since the fecundity loss is unrelated to hormonal change or sexual function compromise. 1 Female sterilization represents around 19% of contraception use in developing countries. In Indonesia, with the increasing proportion of women aged 35–49 and an increasing number of contraceptive prevalence rates (CPR), the estimate of female sterilization needs is around 28 million women. 2 However, in some patients who previously underwent female sterilization, due to several reasons they want to have children again. Accordingly, tubal reanastomosis is one possible way to conceive for women desiring fertility who previously underwent tubal sterilization. This method may be preferred especially in low-resource settings or in developing countries because of its cost-effectiveness and feasibility. 2 Tubal reanastomosis is a microsurgical technique to recanalize fallopian tubes after previous sterilization. This procedure involves a loupe or microscope for magnifying the tubes during reanastomosis procedure. Minimally invasive laparoscopy or robotic-assisted surgery are other alternative ways available to perform tubal reanastomosis surgery. 3 The outcome and success rate following tubal reanastomosis differ among patients, indicating several factors may affect the outcome. This study presents one report of a successful procedure of tubal reanastomosis. We also discuss the possible factors to improve the success rate of tubal reanastomosis. Systematic literature searching was done from the MEDLINE database.